2015
DOI: 10.1074/jbc.m114.627869
|View full text |Cite
|
Sign up to set email alerts
|

How the Location of Superoxide Generation Influences the β-Cell Response to Nitric Oxide

Abstract: Background: Although nitric oxide inhibits ␤-cell function, the impact of superoxide on nitric oxide signaling remains unknown. Results: Superoxide produced within ␤-cells inhibits nitric oxide-dependent responses, whereas extracellular generation does not. Conclusion:The reaction of nitric oxide with superoxide regulates the ␤-cell response to nitric oxide. Significance: The location of radical generation dictates the functional response of ␤-cells to reactive species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
(77 reference statements)
2
19
0
Order By: Relevance
“…In their report (1), the authors strengthen doubts that peroxynitrite is a main culprit for ␤-cell dysfunction and death in type 1 diabetes, confirming previous studies (2).…”
supporting
confidence: 79%
“…In their report (1), the authors strengthen doubts that peroxynitrite is a main culprit for ␤-cell dysfunction and death in type 1 diabetes, confirming previous studies (2).…”
supporting
confidence: 79%
“…Menadione stimulates DDR activation only at the concentration of 60 mmol/L ( Fig. 3C) (34). H 2 O 2 also stimulates DDR activation yet does not impair camptothecin-induced DDR activation at low concentrations ( Fig.…”
Section: Selectivity Of Reactive Oxygen and Nitrogen Species As Inhibmentioning
confidence: 80%
“…Reactive oxygen species (ROS) and nitrogen species (RNS) activate distinct signaling pathways in b-cells (34,35). For determination of whether other forms of ROS or RNS suppress DDR activation, INS 832/13 cells were treated for 1 h with camptothecin in the presence or absence of DPTA/NO, SIN-1 (peroxynitrite donor), menadione (superoxide generator), or H 2 O 2 ( Fig.…”
Section: Selectivity Of Reactive Oxygen and Nitrogen Species As Inhibmentioning
confidence: 99%
“…We have shown that ␤ cells lack the ability to generate superoxide and therefore peroxynitrite in response to cytokines (35,49). When forced to generate peroxynitrite following treatment with the superoxide-generating redox cycler menadione and a chemical donor of nitric oxide, superoxide scavenges nitric oxide and protects ␤ cells from nitric oxide-mediated decreases in cellular ATP, oxidative metabolism, and the induction of nitric oxide-dependent gene expression (35,49). This protection from nitric oxide-mediated damage occurs under conditions where ␤ cells generate peroxynitrite to levels that are comparable to the levels generated by activated macrophages (35).…”
Section: Discussionmentioning
confidence: 99%